2018
DOI: 10.1016/j.lrr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a specific extracellular matrix signature is a favorable prognostic factor in acute myeloid leukemia

Abstract: Relapse of acute myeloid leukemia (AML) is still dramatically frequent, imposing the need for early markers to quantify such risk. Recent evidence point to a prominent role for extracellular matrix (ECM) in AML, but its prognostic value has not yet been investigated. Here we have investigated whether the expression of a 15-ECM gene signature could be applied to clinical AML research evaluating a retrospective cohort of 61 AML patients and 12 healthy donors. Results show that patients whose ECM signature expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Previous studies of ECM expression at the mRNA level have described a 15-ECM gene expression signature that is associated with survival for patients receiving intensive antileukemic treatment [ 33 , 34 , 35 ]. Ten of the proteins encoded by these 15 genes could be detected in our present proteomic studies ( Table S8 ), and five of them were not released at detectable levels by MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of ECM expression at the mRNA level have described a 15-ECM gene expression signature that is associated with survival for patients receiving intensive antileukemic treatment [ 33 , 34 , 35 ]. Ten of the proteins encoded by these 15 genes could be detected in our present proteomic studies ( Table S8 ), and five of them were not released at detectable levels by MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, in a recent study, we evaluated the level of the expression of matrisome genes in 10,487 patients across 32 tumor types using TCGA data and demonstrated that matrisome gene expression can segregate different tumor types [ 31 ]. Last, “omic” technologies have uncovered ECM genes and proteins whose levels are predictive of cancer patient outcome [ 23 , 25 , 32 , 33 , 34 ]. However, while mutations in ECM genes have been linked to a plethora of diseases and syndromes [ 35 ], no study has focused on determining the presence and extent of genomic alterations and mutations in ECM genes in cancers, a crucial piece of information to further understanding of the tumor microenvironment (TME) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 21,380 new AML cases and 10,590 deaths from this disease were reported in 2017 by the American Cancer Society. 1 Despite the advancements in modern chemotherapy, the prognosis of patients with AML has remained poor. 2 , 3 Identifying the mechanisms involved in AML metastasis may lead to innovative treatment methods and improved patient outcomes.…”
Section: Introductionmentioning
confidence: 99%